The Effectiveness of Public Information Disclosure Policies in State Religious Universities: A Study of Satisfaction Surveys, Digital Analysis, and Information Services at UIN Sunan Gunung Djati Bandung - Priatna, Tedi (Civiliza Publishing, Indonesia., 2025)
This study aims to analyze the effectiveness of public information disclosure policies at UIN Sunan Gunung Djati Bandung through a study of satisfaction surveys, digital analysis, and public information services. This study uses a qualitative descriptive approach supported by quantitative analysis obtained from user survey results, digital traffic data, and documentation of public information services recorded by PPID. The results of the study show that the public information disclosure policy at UIN Bandung has been quite effective in providing access to information that is transparent, easy to reach, and in accordance with regulations. The level of public satisfaction is relatively high, supported by the increase in digital access over time, as well as the responsiveness of public information services. However, there are several areas for improvement, especially related to digital channel optimization, sustainability of socialization, and improving the quality of face-to-face services. These findings affirm the importance of synergy between policies, digital technology, and public services in realizing an accountable and participatory university.